The Paratext of Levon Shant’s drama “Ancient Gods” (remarks) - Asatryan, Karine (Bulletin of Yerevan University B: Philology, 2025)
Among the paratextual units of drama, remarks are important structural elements in a drama text as well as in stage art for a theatrical interpretation of a play. These author’s verbal markings of a drama text are non-verbally expressed on stage. The stage space is built via descriptions of events, surroundings, relation of space and time through remarks, while remarks that accompany the characters’ dialogues and describe their physical actions and inner world greatly contribute to the communicative expressiveness of artistic speech. Apart from their interpretational meaning, remarks are semantic components of the artistic structure in a literary text, which take part in the construction of the totality of events and the discovery of the subtextual meaning of dramatic actions. The article discusses the paratext of Levon Shant’s drama “Ancient Gods” from a structural and semantic point of view, focusing, in particular, on introductory and inter-speech remarks, as well as the paratextual connection between the drama text itself (the text of dialogues and monologues) and the title components of the scenes.